Implementation of Cloud Computing and Internet of Things (IoT) by Performance Evaluation - Jiran Sithiyopasakul; Tuanjai Archevapanich; Saran Sithiyopasakul; Attasit Lasakul; Boonchana Purahong; C. Benjangkaprasert (My University, 2024)
The integration of cloud computing and the Internet of Things (IoT) holds transformative potential across diverse industries. Performance assessment is essential to gauge the quality and efficiency of cloud computing and IoT systems. This paper presents a comprehensive performance evaluation of cloud computing and IoT systems, focusing on three major platforms: Amazon Web Services (AWS), Google Cloud Platform (GCP), and Microsoft Azure. Experimental results encompass various scenarios, including normal operation, heavy load conditions, IoT applications, and scalability testing. The outcomes reveal distinct performance metrics such as response time, throughput, latency, and reliability for each cloud platform.
Keywords: IoT and Edge/Fog Computing; Cloud Computing and Resource Management; Blockchain Technology Applications and Security